Some Problems of Human Rights Education - Sharan, Shankar (JOURNAL OF INDIAN EDUCATION, 2009)
Human Rights is becoming a very significant concept in the contemporary world. At the same time its use and misuse is also a much contested area. Theoretical, political and juridical pronouncements on the subject are as diverse as are the countries in the world. In the event, the Human Rights education becomes a tricky subject. Various agencies, organizations and individuals interpret the very concept of Human Rights in hugely different ways, frequently contradicting each other. On the other hand their uses for covert and overt purposes in the international arena generate heated polemics. Therefore, we in India have to be careful while imparting Human Rights education through various channels and to a range of target groups. This essay tries to underline some of the essential issues in this regard. If the conceptual differences, political overtones and activist agenda are not carefully taken into account, the Human Rights education cannot serve a positive purpose in this country. Our teachers and educationists must care for all the nuances and should not be carried away by any one or other declaration on the subject.